2019
DOI: 10.3102/0162373719865561
|View full text |Cite
|
Sign up to set email alerts
|

Making the Cut: The Effectiveness of Teacher Screening and Hiring in the Los Angeles Unified School District

Abstract: Many schools and districts have considerable discretion when hiring teachers, yet little is known about how that discretion should be used. Using data from a new teacher screening system in the Los Angeles Unified School District (LAUSD), we find that performance during screening, and especially performance on specific screening assessments, is significantly and meaningfully predictive of hired teachers’ evaluation outcomes, contributions to student achievement, attendance, and mobility. However, applicants’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
3
11
1
1
Order By: Relevance
“…Because of vendor guidelines, these applicants would not be told they were basically ineligible for building-level interviews. To summarize, prescreeners seem to act as an extremely high hurdle in the hiring process, echoing some recent findings (Bruno & Strunk, 2019; Goldhaber et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Because of vendor guidelines, these applicants would not be told they were basically ineligible for building-level interviews. To summarize, prescreeners seem to act as an extremely high hurdle in the hiring process, echoing some recent findings (Bruno & Strunk, 2019; Goldhaber et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Results indicated that ratings on the screening instruments were significant predictors of value-added scores in math and of teacher attrition but were not predictive of teacher absences. Similarly, Bruno and Strunk (2019) examined Los Angeles Unified School District’s new hiring sequence, which included assigning scores for eight different measures of teacher quality (e.g., writing sample, teaching of a sample lesson). They found that candidates’ screening scores were meaningfully predictive of novice teachers’ early evaluation scores and their students’ test scores in mathematics and English.…”
Section: Review Of Selected Literaturementioning
confidence: 99%
“…Our finding of math VAM quality gaps across FRL bins suggests that schools, districts, and states should be cognizant of the ways in which they distribute teachers, particularly if schools are trying to adhere to the Endrew F. court decision to ensure equitable outcomes for SWDs. Existing literature shows that our case is not unique; schools tend to assign novice or less-effective teachers to classes with larger proportions of low-performing students (e.g., Bruno & Strunk, 2019;Kalogrides & Loeb, 2013;Lankford et al, 2002).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 97%
“…For teachers hired/rehired SY2014–2015, we have composite hiring scores based on application information (e.g., licensure, grade point averages), professional references, writing samples, interviews, and sample lesson demonstrations. Details can be found in Online Appendix C and Bruno and Strunk (2019). All hiring scores are standardized by year.…”
Section: Datamentioning
confidence: 99%
“…Любопытным представляется также повышенное внимание, которое уделяют за рубежом процессу рекрутинга молодых учителей в школы. В ряде работ об отборе кандидатов на учительские должности содержатся конкретные рекомендации по его организации [18,19].…”
Section: обзор литературыunclassified